Analyzing the sustainability of the environmental and socio-economic externalities of the Limpopo National Park (Mozambique) since its institution - Malate, Juvência Yolanda; Fierravanti, Angelo; Sitoe, Almeida Alberto; Tibério, Manuel Luís; Lopes, Luís Filipe Gomes (Frontiers in Conservation Science, 2025)
The institutionalization of the Limpopo National Park (LNP) presented a significant challenge in balancing environmental conservation goals with the needs of local communities. As a component of the Great Limpopo Transfrontier Park (GLTP), the LNP has benefited from collaborative initiatives between Mozambique, South Africa, and Zimbabwe, which have facilitated access to financial and technical resources for the rehabilitation of wildlife populations. Specifically, as several communities remain partially or entirely unsettled, conflicts between humans and wildlife have intensified, with negative implications for both agricultural crop production and livestock management. Nevertheless, the strategies implemented have achieved significant success in preserving biodiversity by facilitating the free movement of wildlife and reducing commercial poaching. In this context, our review aimed primarily to critically analyze the phases related to both the creation and the evolution of the LNP, also considering the relevant role of local traditional practices in defining its management strategy. Secondly, we proposed a strategy that, while imposing restrictions on land use, also incorporates traditional techniques to repel wildlife and reduce habitat fragmentation, potentially contributing to the decrease of interactions between humans and wildlife. Our results highlight the need for a management strategy for the LNP that, unlike the current one, better harmonizes ecosystem protection actions with the basic needs and practices of local communities. In fact, even with the legal limitations in place, many families living within the park continue to rely primarily on subsistence agriculture, which, in the long term, may further exacerbate the reduction of forest cover. Thus, our findings can provide essential subsidies to more effectively guide the future management of the LNP, ensuring the long-term coexistence of wildlife protection initiatives with the socio-economic resilience of local